The Influence of the Information System Success Model and the Technology Acceptance Model on the Behavioral Intention of Specialist Doctors to use Electronic Medical Records For Inpatient Care Unit - Julita D. L. Nainggolan; Duta Liana; Hosizah (GoAcademica Research & Publishing, 2023)
The acceleration of technological developments affects the management of information systems within the hospital, especially in using of Electronic Medical Records (EMR). Behavioral intention to use EMR is the essential factor, the role of user is one of the keys to successful EMR implementation. This study aims to analyze the factors that influence behavioral intention of specialist doctors to use inpatient EMR. Data were obtained through questionnaires using the Likert measuring scale and data analysis was processed using SEM (Structural Equation Modelling). Quantitative analytical research method with cross-sectional design using a total sampling of 144 specialists. Of the total 144 respondents, the majority of respondents were male (59%), aged 40-50 years (30.6%) and had a working period of more than 20 years (25.7%). Hypothesis analysis found that there was an effect of system and information quality on perceived ease of use and usefulness. System quality, perceived ease of use and usefulness influence behavioral intention, while information quality has no effect, but indirectly influences behavioral intention through perceived ease of use and usefulness. Service quality has no effect on perceived ease of use, perceived usefulness, and behavioral intention. Perceived usefulness has the greatest influence on behavioral intentions to use inpatient EMR. As an implication of this study, it was found that it is necessary to optimize the inpatient EMR system in the aspects of reliability and connectivity.